Ramadan et « sauce à la souris ». Interdits et compromis alimentaires entre musulmans et animistes d’Afrique occidentale d’après le récit de René Caillié au début du XIXe siècle - Monique Chastanet (Afriques)
During his travel to Timbuktu in 1827–1828, René Caillié was interested in the lifestyle of the Muslims traders, his fellow travellers, and of the animist villagers along the caravans’ path. This was an exceptional experience in many ways, although this testimony must be approached critically. In particular, René Caillé described the eating practices of the traders and the animists, and of the former with the latter, according to their religious affiliations. These behaviours provide a contrasting picture of the relations between animists and Muslims, which can consist of prohibitions, tolerances, or compromises on the part of the ‘Mandingo’ traders. These practices also show different ways of being a Muslim in Sudano-Sahelian Africa at the beginning of the 19th century, depending on the pacific or expansionist tendencies of Islam, on the needs of long-distance trade, and on the prevalence of some local habits.